INVESTIGATION OF NUCLEAR EMULSIONS IN TERMS OF NEUTRON DOSIMETRY - Lužová, Martina; Zaitsev, Andrei A; Bradnová, Věra; Ambrožová, Iva; Kákona, Martin; Štěpán, Václav; Košťál, Michal; Kolros, Antonín; Ploc, Ondřej; Zarubin, Pavel I (Radiation protection dosimetry, 2019)
Neutron detection using nuclear emulsions can offer an alternative in personal dosimetry. The production of emulsions and their quality have to be well controlled with respect to their application in dosimetry. Nuclear emulsions consist mainly of gelatin and silver halide. Gelatin contains a significant amount of hydrogen, which can be used for fast neutron detection. The addition of B-10 in the emulsion is convenient for thermal neutron detection. In this paper, standard nuclear emulsions BR-2 and nuclear emulsions BR-2 enriched with boron produced at the Slavich Company, Russia, were applied for evaluation of fast and thermal neutron fluences. The results were obtained by calculation from the presumed emulsion composition without prior calibration. Evidence that nuclear emulsions used in the experiment are suitable for neutron dosimetry is provided.
Keywords: bromidy; Gelatin; emulze; rychlé neutrony; vodík; lithium; Boron; Radiometry; fantomy radiodiagnostické; Image Processing, Computer-Assisted; Lithium; Calibration; neutrony; Fast Neutrons; radiometrie; kalibrace; Hydrogen; sloučeniny stříbra; počítačové zpracování obrazu; Bromides; Phantoms, Imaging; želatina; helium; Emulsions; bor; Neutrons; Silver Compounds; Helium